1999
DOI: 10.1007/s100510050966
|View full text |Cite
|
Sign up to set email alerts
|

Discrete scale invariance in viscous fingering patterns

Abstract: PACS. 47.20.Ma Interfacial instability - 83.10.Ji Fluid dynamics (nonlinear fluids) - 68.10.-m Fluid surfaces and fluid-fluid interfaces,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…In this case the magnetosphere should be devoid of matter and the radio pulsar mechanism should turn on with a strong pulsar wind preventing further accretion (see e.g., Stella et al 1994;Burderi et al 2001). This is what is currently thought to occur in the radio-pulsar phase of the three transitional pulsars recently discovered (Archibald et al 2009;Papitto et al 2013;Bassa et al 2014;Patruno et al 2014;Roy et al 2014Roy et al , 2015Stappers et al 2014) and in the quiescence phase of SAX J1808.4−3658 (Homer et al 2001;Burderi et al 2003;). The fact that in SAX J1808.4 −3658 the X-ray luminosity increases by three orders of magnitude right after reaching the luminosity minima on a very fast timescale of 1-2 days (see Figures 2 and 3) suggests that the radio pulsar mechanism does not turn on, although a very rapid switch cannot be excluded at the moment.…”
Section: Accretion Flow Geometrymentioning
confidence: 96%
“…In this case the magnetosphere should be devoid of matter and the radio pulsar mechanism should turn on with a strong pulsar wind preventing further accretion (see e.g., Stella et al 1994;Burderi et al 2001). This is what is currently thought to occur in the radio-pulsar phase of the three transitional pulsars recently discovered (Archibald et al 2009;Papitto et al 2013;Bassa et al 2014;Patruno et al 2014;Roy et al 2014Roy et al , 2015Stappers et al 2014) and in the quiescence phase of SAX J1808.4−3658 (Homer et al 2001;Burderi et al 2003;). The fact that in SAX J1808.4 −3658 the X-ray luminosity increases by three orders of magnitude right after reaching the luminosity minima on a very fast timescale of 1-2 days (see Figures 2 and 3) suggests that the radio pulsar mechanism does not turn on, although a very rapid switch cannot be excluded at the moment.…”
Section: Accretion Flow Geometrymentioning
confidence: 96%
“…This variability reinforced the prediction, first made by Hill et al (2011), that the system could harbour an active radio MSP, sharing similar properties with J1023. Follow-up observations in the radio finally succeeded in detecting pulsations at a period of 1.69 ms (Roy et al 2014).…”
Section: Xss J12270-4859mentioning
confidence: 96%
“…A similar system is the LMXB XSS J12270−4859. In recent years, radio, optical, and X-ray observations of this system suggested that, since the end of 2012, it may have switched to a MSP phase (Bassa et al 2014;Bogdanov et al 2014;de Martino et al 2015), and the detection of 1.69 ms radio pulsations provided compelling evidence for the change of state (Roy et al 2014). …”
Section: Based On Observations Made With European Southern Observatormentioning
confidence: 97%
“…The swings between rotation and accretionpowered behaviour recently observed from IGR J18245-2452 (Papitto et al 2013;Pallanca et al 2013;Ferrigno et al 2014;Linares et al 2014) PSR J1023+0038 (Archibald et al 2009;Stappers et al 2013;Patruno et al 2014), and XSS J12270-4859 (Bassa et al 2014;Papitto et al 2014;Roy et al 2014;Bogdanov et al 2014) demonstrated that NSs in some LMXBs alternate cyclically between rotation and accretion-powered states on short time-scales of a few years, or shorter.…”
Section: Introductionmentioning
confidence: 93%